IMPROVEMENT OF PROFESSIONAL TRAINING FOR THE MILITARY- INDUSTRIAL COMPLEX - Anatoly V. Ivanov; Oleg V. Kuznetsov (Высшее образование в России)
Strengthening of the defense capability and the national security of the country in the faceof the contemporary challenges requires the improvement of professional training, retraining, advanced training, additional training of personnel and specialists for the defense industries. The article defines the main areas of such improvement based on the analysis of the available human resources of the military-industrial complex organizations. We used the method of content analysis of normative legal acts regulating the functioning of the defense industry in general and the organizations of the military-industrial complex inparticular. The article formulates the conclusions and practical recommendations to public authorities on the implementation of innovations related to professional training of workers and specialists of the military-industrial complex.